Whooping cough epidemics in London, 1701-1812: infection dynamics, seasonal forcing and the effects of malnutrition. - Duncan, C; Duncan, S; Scott, S (1996)
Time series analysis of the London Bills of Mortality, 1701-1812, reveals that whooping cough appeared as a lethal endemic disease after 1700 with epidemics of progressively increasing amplitude after 1720. The interepidemic period changed from 5 years (1720-1750) to 3 years (1750-1785) before returning to 5 years during 1785-1812. The epidemiology of whooping cough can be described by the mathematics of linearized dynamic systems and the interepidemic interval is determined by population size and susceptibility. The latter was governed by fluctuating levels of malnutrition, which were directly associated with oscillations in the wheat prices. It is suggested that the epidemics were driven in 1720-1785 by fluctuating seasonal temperatures which interacted with oscillations in wheat prices to produce an oscillation in susceptibility, but after 1785 the dynamics escaped from the pattern predicted by mathematical theory and the epidemics were apparently driven only by the wheat prices which generated a regular oscillation in susceptibility. The results emphasize the importance of an adequate nutritive level in combating whooping cough in the Third World today where it remains a lethal disease in children because of immunodeficiency linked to fluctuating and severe malnutrition which is often a consequence of crop cycles.